2013
DOI: 10.1007/s00265-013-1631-5
|View full text |Cite
|
Sign up to set email alerts
|

A test of multiple hypotheses for the function of call sharing in female budgerigars, Melopsittacus undulatus

Abstract: In many social species group, members share acoustically similar calls. Functional hypotheses have been proposed for call sharing, but previous studies have been limited by an inability to distinguish among these hypotheses. We examined the function of vocal sharing in female budgerigars with a two-part experimental design that allowed us to distinguish between two functional hypotheses. The social association hypothesis proposes that shared calls help animals mediate affiliative and aggressive interactions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 110 publications
(169 reference statements)
3
50
0
Order By: Relevance
“…In contrast to patterns in zebra finches, we found low levels of FoxP2 mRNA and protein in the MMSt regardless of the vocal status in adult budgerigars. Such persistent down-regulation is consistent with the fact that budgerigars are capable of modifying their contact calls as adults [21]. Previously it has been reported that FoxP2 mRNA expression in adult budgerigars is similar between MMSt and the surrounding striatum [6], a result that differs from ours here.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to patterns in zebra finches, we found low levels of FoxP2 mRNA and protein in the MMSt regardless of the vocal status in adult budgerigars. Such persistent down-regulation is consistent with the fact that budgerigars are capable of modifying their contact calls as adults [21]. Previously it has been reported that FoxP2 mRNA expression in adult budgerigars is similar between MMSt and the surrounding striatum [6], a result that differs from ours here.…”
Section: Discussionsupporting
confidence: 90%
“…When call learning is restricted to a critical period early in life, shared signals have the potential to constrain movement among families, social groups and populations (Sewall, 2009; Wright, 1996). In many taxa, however, call production learning can continue into adulthood and such flexibility may be particularly important for encoding changing social relationships and facilitating flexibility in social bonds (Dahlin et al, 2014; Salinas-Melgoza & Wright, 2012; Sewall, 2009). …”
Section: Patterns Of Contact Call Learningmentioning
confidence: 99%
“…Similarly, playbacks of signature whistle calls in wild bottlenose dolphins, Tursiops truncatus , only elicited responses from individuals when their own whistles were broadcast (King & Janik, 2013). Budgerigars, Melopsittacus undulatus , produce contact call variants that are shared with mates and flock members, as well as unshared variants; shared calls contain acoustic signatures of both the sender and receiver (Dahlin et al, 2014), and hearing playback of shared and nonshared calls results in different patterns of brain activity in receivers (Brauth et al, 2002). Such differential neural response is consistent with individuals being sensitized to calls like their own and offers a mechanism that could ensure that receivers recognize and attend to the calls of companions, even in noisy environments (Tyack, 2008).…”
Section: Hypotheses For the Evolutionary Origins Of Call Learningmentioning
confidence: 99%
“…Without data about population genetics, forming conclusions about the origin and maintenance of geographic variation in vocal characteristics of palm cockatoos would be undermined by the psittacine ability to adjust vocally to their social environment (see Farabaugh et al 1994;, Dahlin, et al 2014. To guide further research, we suggest two mutually plausible explanations for the variation in vocal characteristics documented here; summarized as the dynamic historical biogeography of CYP, and contemporary biogeographical influences.…”
Section: Vocalization Patterns and Biogeographymentioning
confidence: 85%
“…Parrots are known to imitate social companions in captivity (e.g. budgerigars Melopsittacus undulatus, Farabaugh et al 1994;Dahlin et al 2014) making social adaptation a likely explanation for similar results in other species (Wright 1996;Baker 2000Baker , 2003 and may explain discreet short whistle types in geographically separate populations of phylopatric palm cockatoos.…”
Section: Between Population Analyses Of Common Contact Callsmentioning
confidence: 91%